GREEN ADVERTISEMENT, GREEN LOYALTY AND ENVIRONMENTAL VALUE INFLUENCE ORGANIC APPAREL PURCHASE BEHAVIOUR – AN INSIGHT FROM BANGALORE CITY, INDIA - Mishra, Prachi; Devakumar, G. (International Journal of Psychosocial Rehabilitation, 2020)
With growing awareness on environmental impacts, consumers nowadays are keen on exploring green products. Green buying behavior is a necessity today for companies to promote sustainable practices in environmental era. Especially so in textile industry which is one of the highest polluting sectors worldwide. Organic apparel has been introduced in market as an alternative towards conventional clothing consumption and to encourage sustainable consumption habits. Hence, the purpose of this study was to examine the influence of green advertisement, green loyalty and environmental value towards organic apparel purchase behaviour. A quantitative approach was adopted to gather data through structured questionnaire survey from 302 respondents. SPSS tool was adopted to carry out multiple regression analysis, independent t test and one-way ANOVA towards hypotheses testing. Green advertisement, environmental value and green loyalty plays significant role in impacting organic apparel purchase behavior as per the findings of this study. Suggestions were given towards re-orientation of marketing strategies to increase demand for organic apparel products so as to support sustainability linked initiatives by organic apparel companies